097 An undisputed case of left hand weakness. Issue 6 (27th May 2022) - Morrison, Hamish; Walton, Edward; Fox, Mike; Stevens, James
Abstract : Introduction: Neurogenic thoracic outlet syndrome (NTOS) is a rare and sometimes overlooked cause of upper limb pain, weakness and disability and presents to a range of different healthcare professionals. Here we present a case of severe NTOS with characteristic clinical, radiological and electroclinical findings. History: A 16 year old right-handed female presented with a two year history of progressive symptoms affecting her left hand. Initially she noticed weakness affecting initially the 4thand 5thleft digits which progressed to involve the whole hand. She described a burning sensation affecting the medial aspect of her left forearm at night. Examination: Examination of the left arm revealed decreased bulk of the thenar, hypothenar and inter- ossei intrinsic muscles of the hand, power diminished to grade 4 in the left ADM, APB, FDIO and to grade 4+ in left EDC, and altered sensation in the T1 dermatome. Investigations: A lordotic chest radiograph revealed bilaterally elongated C7 transverse processes, a finding confirmed on retrospective review of the brachial plexus MRI, which also revealed bilateral grade 1 cervical ribs and increased signal on STIR sequence of the left C8 and T1 nerve roots. Nerve conduction studies revealed electroclinical evidence of a left lower trunk brachial plexopathy. Outcome: The patients neuropathic pain responded to low dose gabapentin. She was assessed at the Peripheral Nerve Injuries Unit at RNOH Stanmore and recently underwent successful left thoracic outlet decompression. hamish.morrison@nhs.net